Early Recognition and Treatment of Hemophagocytic Lymphohistocytosis in A Child with the Early Symptom of DIC - Zheng, Wanqi; Wang, Yuchuan; Liu, Zhengjuan; Yu, Xinbo; Sun, Zhao (Archives of Clinical and Medical Case Reports, 2020)
Background: Hemophagocytic lymphohistocytosis (HLH) is a potentially fatal multiple organ inflammatory response syndrome that is characterized by proliferation of histiocytes and inflammatory factor storm. The disease progress varies fast and has a high death rate. Disseminated intravascular coagulation (DIC) is one of the leading causes of death in HLH. Here, we reported a child suffered from secondary HLH with the early symptom of DIC. Case Description: A 2.5 year-old boy was hospitalized in our ward of the Second Affiliated Hospital of Dalian Medical University due to persistent high fever. The patient had the early manifestation of DIC, which was different from sepsis, and also had progressive pancytopenia, high serum ferritin level, hepatic dysfunction, hypertriglyceridemia, elevated soluble IL-2 receptor level, and hemophagocytosis in the bone marrow. With early treatment of HLH, the patient recovered rapidly without recurrence. Conclusion: DIC can appear in the early phase of HLH, and also note that it should be distinguished with sepsis. Early diagnosis and reasonable therapy are very important to improve the prognosis of HLH.